2018
DOI: 10.1111/hiv.12680
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of HIV positive Ethiopian elite controllers in both Africa and Israel

Abstract: Objectives HIV elite controllers (ECs) are a unique subgroup of HIV-positive patients who are long-term virologically suppressed in the absence of antiretroviral treatment (ART). The prevalence of this subgroup is estimated to be < 1%. Various cohorts of ECs have been described in developed countries, most of which have been demographically heterogeneous. The aim of this study was to identify ECs in two large African cohorts and to estimate their prevalence in a relatively genetically homogenous population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…In this cohort with semestrial viral load monitoring and a mean of six viral load measurements per person, 1.8% of 1023 adults were classified as HIV-1 controllers, including 0.7% of elite controllers and 1.1% of viremic controllers. These rates are higher than those recently estimated in Uganda and Ethiopia [14,15], and within the range of those found in other continents [4,6,14,15,23]. Unlike studies in Europe or North America, the HIV-1 controllers in our study and those in the Ugandan and Ethiopian studies were mostly female, which is consistent with HIV epidemic characteristics in sub-Saharan Africa.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this cohort with semestrial viral load monitoring and a mean of six viral load measurements per person, 1.8% of 1023 adults were classified as HIV-1 controllers, including 0.7% of elite controllers and 1.1% of viremic controllers. These rates are higher than those recently estimated in Uganda and Ethiopia [14,15], and within the range of those found in other continents [4,6,14,15,23]. Unlike studies in Europe or North America, the HIV-1 controllers in our study and those in the Ugandan and Ethiopian studies were mostly female, which is consistent with HIV epidemic characteristics in sub-Saharan Africa.…”
Section: Discussionsupporting
confidence: 81%
“…Data on HIV-1 controllers in sub-Saharan Africa are scarce [13][14][15] and opportunities to record new data are getting fewer. In the past, many HIV-1-infected individuals living in sub-Saharan Africa had poor access to routine viral load monitoring before they were put on ART.…”
Section: Introductionmentioning
confidence: 99%
“…This misreporting of HIV status and engagement in care has been described previously (10). Although, there is a possibility that some are elite controllers, this proportion is much higher than what would be expected based on several studies of elite controllers in Africa (39‐41). Thus, although bio‐behavioural surveys are sometimes the only way to assess MSM and other KPs engagement in care due to the difficulty of identifying them in routine HIV programme data (42,43), these data reiterate the shortcomings of relying on self‐reported data to estimate HIV status and ART coverage and the potential utility of testing for plasma ART levels in addition to viral load (44).…”
Section: Discussionmentioning
confidence: 76%
“…A survey conducted by the US Department of Defense found that among HIV+ military personnel, only 25/4586 (0.55%) were EC and 153/4586 (3.34%) were VC [15] . The landscape is similar in most of Africa, with cohorts in Uganda (0.26%), Botswana (0.3%), South Africa (1.25%), and Ethiopia (1.17%, 0.6%) all reporting very few controllers of either type [48] , [49] , [50] , [51] , [52] . Our own data (not shown) from the Abbott Global Surveillance program, characterizing specimens from over 60 countries for nearly 30 years, mirrors these trends.…”
Section: Discussionmentioning
confidence: 99%